1999
DOI: 10.1016/s0735-1097(98)00606-8
|View full text |Cite
|
Sign up to set email alerts
|

The economic consequences of available diagnostic and prognostic strategies for the evaluation of stable angina patients: an observational assessment of the value of precatheterization ischemia

Abstract: Observational assessments reveal that stable chest pain patients who undergo a more aggressive diagnostic strategy have higher diagnostic costs and greater rates of intervention and follow-up costs. Cost differences may reflect a diminished necessity for resource consumption for patients with normal test results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
142
0
24

Year Published

1999
1999
2017
2017

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 322 publications
(173 citation statements)
references
References 24 publications
7
142
0
24
Order By: Relevance
“…An important conclusion of our article, as previously shown by both our group and others, is that cost-effectiveness is achieved only when the use of SPECT is limited to appropriate patient populations; that is, patients at intermediate to high prescan likelihood of coronary artery disease (CAD). [2][3][4] In both our study and previous studies, SPECT was found to yield clinical value and be cost-effective when used in appropriate populations, and these costs were significantly lower than those associated with testing in unselected patients.…”
Section: Responsesupporting
confidence: 70%
“…An important conclusion of our article, as previously shown by both our group and others, is that cost-effectiveness is achieved only when the use of SPECT is limited to appropriate patient populations; that is, patients at intermediate to high prescan likelihood of coronary artery disease (CAD). [2][3][4] In both our study and previous studies, SPECT was found to yield clinical value and be cost-effective when used in appropriate populations, and these costs were significantly lower than those associated with testing in unselected patients.…”
Section: Responsesupporting
confidence: 70%
“…Scintigraphic studies have shown imaging data to be of independent and incremental prognostic value to standard investigations, and selective application of this modality in combination with standard risk variables 22 may reduce expenditure on subsequent invasive investigations, while at the same time having no adverse impact on outcome. 23 Previous studies with exercise echocardiography have indicated that the imaging component of this test adds incremental and independent information to the results of standard exercise testing. [7][8][9][10][11][12] A normal exercise echocardiogram is associated with a risk of Ͻ1% per year over the first 6 years of follow-up, with a subsequent small increase that most likely reflects progressive coronary artery disease.…”
Section: Assessment Of Risk In Patients With Stable Chronic Coronary mentioning
confidence: 99%
“…Another important point in this manuscript suggests the cost effectiveness of choosing diagnostic modalities. To find out the cost effectiveness in the diagnostic modalities, further investigations are important in a prospective cohort (27,28).…”
Section: Initial Diagnostic Modalitymentioning
confidence: 99%